A simple way to reduce heat stress in laying hens as judged by egg laying, body weight gain and biochemical parameters - Şahin, Kazım; Küçük, Ömer (Akademiai Kiado Zrt, 2001)
This study was designed to test the effects of feed withdrawal and darkening on the performance, triiodothyronine (T3), thyroxine (T4), thyroid-stimulating hormone (TSH), adrenocorticotropic hormone (ACTH), and some blood serum metabolite and mineral concentrations of laying hens reared at high ambient temperatures ranging from 25 to 35 degreesC. Ninety, 16-week-old hens (Ross Brown) were divided into 3 groups, 30 hens each. The first group was used as control. Hens in the second group (feed withdrawal) were subjected to feed removal from 14:00 to 18:00, and hens in the third group (darkening) were subjected to light restriction from 14:00 to 18:00 using black curtains. Liveweight, feed intake, and egg production were higher (P < 0.01) in the feed withdrawal and darkening groups, particularly in the darkening group, than in the control. Water intake was higher in the control group compared with the feed withdrawal and darkening groups (P < 0.01). T3, T4, and TSH concentrations in the serum were higher (P < 0.01), whereas ACTH serum concentration was lower (P < 0.01) in the feed withdrawal and darkening groups compared with the control. The haematocrit was higher in the feed withdrawal and darkening groups compared with the control (P < 0.01). Darkening and feed withdrawal treatments increased serum glucose, urea-N, uric acid, albumin, triglyceride, cholesterol, Ca, P, Na, and K concentrations, also the activities of amylase and alkaline phosphatase, but did not influence the activities of serum glutamic-oxaloacetic transaminase (SGOT) and serum glutamic pyruvic transaminase (SGPT). The present study found that feed withdrawal and darkening, particularly darkening, at high temperatures during the summer months offer a good management practice to reduce heat stress related depression in feed intake and egg production in laying hens.
Keywords: laying hen; heat stress; darkening; feed withdrawal; performance